2013
DOI: 10.4172/2329-8901.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Bifidobacterium Lactis hn019 and Release of Biogenic Compounds in Unfermented and Fermented milk is affected By Chilled Storage at 4°C

Abstract: Development of dairy products containing bifido bacteria is one of the main focuses in the food industry, considering the health benefits attributed to its survival through gut intestinal tract and the liberation of biogenic compounds. In order to evaluate the effect of process conditions on survival of Bifidobacterium animalis subsp. Lactis HN019 and release of biogenic compounds during cold storage two technological processes were employed: (i) addition of Probiotic (unfermented bifido milk; UFBM) and (ii) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These data corroborate with the hypothesis that it is not just the viable microorganism or metabolites produced during fermentation, but a combination of both that are able to perform the best interaction between the probiotic and the host. Non-viable cells plus fermentation metabolites could stimulate the PP formation despite that no statistical differences were noted (FBMHT), merely metabolites produced during the fermentation process (Bogsan et al, 2013) were not enough to properly stimulate the immune system (Fig. 4).…”
Section: Effects In Immune Activation In the Gut Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…These data corroborate with the hypothesis that it is not just the viable microorganism or metabolites produced during fermentation, but a combination of both that are able to perform the best interaction between the probiotic and the host. Non-viable cells plus fermentation metabolites could stimulate the PP formation despite that no statistical differences were noted (FBMHT), merely metabolites produced during the fermentation process (Bogsan et al, 2013) were not enough to properly stimulate the immune system (Fig. 4).…”
Section: Effects In Immune Activation In the Gut Mucosamentioning
confidence: 99%
“…In order to enhance mucus production (Grzeskowiak et al, 2011) and start low grade inflammation (Perdigon, Galdeano, Valdez, & Medici, 2002), these data suggested that metabolites produced during the B. lactis HN019 fermentation (Bogsan et al, 2013) or modification of the probiotic functionality are required, and play a key role in the interaction between host and functional foods.…”
Section: Weight Profile and Histology Differences Into The Gut Mucosamentioning
confidence: 99%
“…The active substance in this fermented beverage was identified as lactotripeptide metabolically generated in the fermentation pathway. Follow-up studies were able to determine the bioactive metabolites of probiotic bacteria in addition to the antimicrobial substances, such as bacteriocin [30,31], and other beneficial active substances, such as conjugated linoleic acid (CLA) [30][31][32], proteins or peptides [33,34], and polyphenols [35,36]. Taking all these observations into account, biogenics, which makes use of the bioactive metabolites as foods or medicine, was recently advocated as a new concept [24,37].…”
Section: The Concept Of Biogenicsmentioning
confidence: 99%
“…The active substance was lactotripeptides metabolically generated in the fermentation pathway. Follow-up studies were able to determine the bioactive metabolites of probiotic bacteria in addition to the antimicrobial substances, such as bacteriocin ( Ross et al, 2010 ; O’Shea et al, 2012 ), and other beneficial active substances, such as conjugated linoleic acid (CLA; Hayes et al, 2006 ; Ross et al, 2010 ; O’Shea et al, 2012 ), protein or peptides ( Möller et al, 2008 ; Bogsan et al, 2013 ), and polyphenols ( Dharmaraj, 2010 ; Monagas et al, 2010 ). Taking all these observations into account, the new concept, biogenics, which makes use of the bioactive metabolites as foods or medicine, was recently advocated ( Mitsuoka, 2000 , 2014 ).…”
Section: Biogenicsmentioning
confidence: 99%